Construction of biochar heterojunctions decorated with nanoscale zero-valent copper and CeOx for synergistically enhanced Fenton-like degradation of glyphosate - Bo Zuo; Yue Ma; Yudie Guo; Ruipu Wang; Li Guo; Shuxin Huang; Yuchi Chen; Junxia Yu (Journal of Environmental Chemical Engineering, 2026)

NeuProIO: A dual-action solid drug nanoparticle topical formulation for simultaneous intraocular pressure reduction and neuroprotection for glaucoma - Lei Xu; Mu Li; Lin Qi; Tzu-Chen Wang; Dong Liu; Vimalin Jeyalatha Mani; Hsin-Yin Chuang; Qingbo Yang; Ruipu Mu; Samira Mahdi; Da Huang; Honglan Shi; et al. (Chemical Engineering Journal, 2026)

Genomic characterization and stress-responsive divergence of HDZip gene family in grapevine (Vitis vinifera L.) - Xue Li; Wen’e Zhang; Yuan Ma; Xuemiao Wang; Jialin Yang; Dongdong Yu; Ruipu Wang; Xuejun Pan (Genetic Resources and Crop Evolution, 2026)

Gradient elution method for treating the residual ammonium from the weathered crust elution-deposited rare earth tailings - Kejia Wu; Ruipu Wang; Jia Wang; Xiaodi Li; Yuchi Chen; Li Guo; Qingbiao Zhao; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi; Junxia Yu (Minerals Engineering, 2025)

Transforming glyphosate mother liquor into zirconium‑phosphorus composite adsorbent for effective Pb (II) removal from lead‑zinc tailing leachate - Bowen Dong; Ruipu Wang; Shuang Xi; Yuanping Guo; Jing Wang; Yuting Li; Li Guo; Yuchi Chen; Ruan Chi; Jia Wang; Junxia Yu (Journal of Water Process Engineering, 2025)

Revealing novel phytotoxicity pathways in rice under two organophosphate esters exposure: From biotransformation processes to toxic intermediates and systemic metabolic perturbations - Xiaolong Yu; Ruipu Yao; Min Xiao; Xu Jin; Jin Tang; Qianwei Liang; Yuxin Li; Jianteng Sun; Lizhong Zhu (Journal of Environmental Management, 2025)

CO2-mediated selective cracking of n-butane to ethylene over HZSM-5-based catalysts - Zhongdong Zhang; Zhaoshuo Ge; Ruipu Wang; Yangping Lv; Enxi Wu; Chaowei Liu; Qin Wu; Daxin Shi; Kangcheng Chen; Guiyuan Jiang; Hansheng Li; Yaoyuan Zhang (Chemical Engineering Journal, 2025)

A Strategy-Group Evolution Algorithm for Planning of Multi-Stage Activities in Modular Shipbuilding Considering Uncertainty Duration - Qi Zhou; Jinghua Li; Xiaoyuan Wu; Ruipu Dong; Zhichao Xu; Dening Song; Lei Zhou (Journal of Marine Science and Engineering, 2025)
Modular shipbuilding, as a cutting-edge ship construction paradigm, enables parallel manufacturing across workshops and stages—a core advantage that significantly shortens the total shipbuilding cycle, making it pivotal for modern shipyards to enhance productivity. However, this mode decomposes the integrated shipbuilding project into a large number of interdependent sub-activities spanning three key stages (fabrication, logistics, and assembly). Further, the duration of these sub-activities is inherently uncertain, primarily due to the extensive manual operations, variable on-site conditions, and supply chain fluctuations inherent in shipbuilding. These characteristics collectively pose a formidable challenge to project planning that pursues both high efficiency and low cost. To address this challenge, this paper proposes a Strategy-Group Evolution algorithm. First, the modular shipbuilding process scheduling problem is mathematically formulated as a resource-constrained three-stage multi-objective optimization model, where triangular fuzzy numbers are employed to characterize the uncertain sub-activity durations. Second, a two-layered Strategy-Group Evolution algorithm is designed for solving this model: the inner layer comprises 12 practical priority rules tailored to modular shipbuilding’s multi-stage features, while the outer layer adopts a genetic algorithm-based evolution policy to schedule and optimize the assignment of inner-layer rules to activity groups. The core of the Strategy-Group Evolution algorithm lies in dynamically assigning suitable strategies to different activity groups and evolving these assignments toward optimality—this avoids the limitation of a single priority rule for all stages, thereby facilitating the search for global optimal solutions. Finally, validation tests on real cruise ship construction projects and benchmark datasets demonstrate the efficacy and superiority of the proposed Strategy-Group Evolution algorithm.

Unveiling the NIMBY effect in construction and demolition waste landfilling: Factors, paths, and solutions - Bo Yu; Jiayuan Wang; Ruipu Li; Qun Wang; Huanyu Wu; Xiaoxiao Xu; Hongping Yuan; Jian Zuo (Journal of Environmental Management, 2024)

Upcycling waste phosphogypsum as an alternative filler for asphalt pavement - Li Ou; Rui Li; Hongzhou Zhu; Hongduo Zhao; Ruipu Chen (Journal of Cleaner Production, 2023)

Molecular cloning and functional characterization of a seed-specific VvβVPE gene promoter from Vitis vinifera - Peijie Gong; Rong Wei; Yan Li; Ruipu Wang; Yujin Tang; Ling Wang; Huijun Zhu; Yuejin Wang; Chaohong Zhang (Planta, 2019)